Consumer behaviour - Craig-Lees, Margaret; Joy, Sally; Browne, Beverly (Brisbane : John Wiley & Sons, 1995)
This book is about: Internal influences; External influences; Consumer decision making; Macro concerns.
Keywords: Consumer behavior; Consumer behavior